2011
DOI: 10.1007/s00395-011-0194-8
|View full text |Cite
|
Sign up to set email alerts
|

Does mild hypothermia protect against reperfusion injury? The debate continues

Abstract: Mild hypothermia (32-35°C) salvages ischemic myocardium and reduces infarct size in hearts undergoing ischemia/reperfusion. It is clear that a cardioprotective effect is evident when the heart is cooled during ischemia, and the protection is greater as the duration of normothermic ischemia is increasingly limited. The effect of cooling just before and at reperfusion is more controversial. Multiple experimental studies have revealed no effect of mild hypothermia on myocardial infarction when cooling was initiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…However, after re-warming the apoptotic speed rebounds rapidly. Therefore, the time window for mild hypothermia beginning should be actively sought (Tissier et al 2011). One research found that pre-operation hypothermia could reduce the damage of neuron and glia in the reperfusion phase of ischemia/reperfusion brain injury (Yokobori et al 2013).…”
Section: Reviewmentioning
confidence: 99%
“…However, after re-warming the apoptotic speed rebounds rapidly. Therefore, the time window for mild hypothermia beginning should be actively sought (Tissier et al 2011). One research found that pre-operation hypothermia could reduce the damage of neuron and glia in the reperfusion phase of ischemia/reperfusion brain injury (Yokobori et al 2013).…”
Section: Reviewmentioning
confidence: 99%
“…In this particular DCD setting (planned withdrawal of treatment), currently available cooling techniques could effectively reduce cardiac temperature by a few degrees prior to the onset of cardiac ischemia. Secondly, given that multiple methods to rapidly induce mild hypothermia are currently being developed and tested , our results highlight the potential need for rapid cooling techniques in the context of DCD.…”
Section: Discussionmentioning
confidence: 86%
“…The combined results of these studies demonstrate an excellent correlation between the duration of cooling during ischemia and infarct size (Tissier et al, 2011a(Tissier et al, , 2011b. In a review by Tissier and coworkers, the results of 16 studies on the effect of hypothermia during ischemia are summarized in a structured table.…”
Section: Erlingementioning
confidence: 99%
“…The effects of hypothermia immediately before and after reperfusion have been examined in other animal studies, but the cooling methods were often too slow to achieve therapeutic temperatures before reperfusion (Maeng et al, 2006), or the statistical significance was only borderline (Otake et al, 2007). Tissier and coworkers applied rapid liquid ventilation cooling in a rabbit model just before reperfusion and succeeded in reaching therapeutic temperatures without observing any effect on infarct size (Tissier et al, 2007(Tissier et al, , 2011b. In contrast, a reduction in infarct size was found in another rabbit study when hypothermia was initiated 5 minutes before reperfusion (Kanemoto et al, 2009).…”
Section: Timing Speed Of Induction and Duration Of Hypothermiamentioning
confidence: 99%